DESIGN AND DEVELOPMENT OF SELF-MICROEMULSIFYING DRUG DELIVERY SYSTEMS (SMEDDS) OF TELMISARTAN FOR ENHANCEMENT OF IN VITRO DISSOLUTION AND ORAL BIOAVAILABILITY IN RABBIT - Sahoo, Suvendu Kumar; Suresh, Padilam; Acharya, Usharani (International Journal of Applied Pharmaceutics, 2018)
Objective: The main purpose of this investigation was to prepare self-microemulsifying drug delivery system (SMEDDS) for enhancement of oral bioavailability of a poorly water soluble drug telmisartan (TLS), a BCS class II drug by improving its dissolution rate. Methods: Self-Emulsifying Drug Delivery Systems (SEDDS) of TLS were formulated using cinnamon essential oil as the oil phase, Gelucire 44/14 as the surfactant and Transcutol HP as co-surfactant. Drug-excipient interactions were studied by FTIR spectroscopy. The formulations were evaluated for its self-emulsifying ability, clarity, and stability of the aqueous dispersion after 48 h and the phase diagram was constructed to optimize the system. Selected formulations were characterized in terms of droplet size distribution, zeta potential, cloud point and were subjected to in vitro drug release studies. The bioavailability of optimized formulation was assessed in New Zealand white rabbits. Results: By considering smaller droplet size, higher zeta potential and faster rate of drug release the formulation TF9 was chosen as optimized SMEDDS formulations. TF9 was robust to different pH media and dilution volumes, remained stable after three cooling-heating cycles and after stored at 4 Â°C and 25 Â°C for 3 mo without showing a significant change in droplet size. The pharmacokinetic study in rabbits showed SMEDDS have significantly increased the Cmax and area under the curve (AUC) of TLS compared to suspension (P<0.05). Conclusion: SMEDDS can be an effective oral dosage form for enhancing aqueous solubility and improving oral bioavailability of poorly water soluble drugs.